Different phenotypes in vivo are associated with ATPase motif mutations in Schizosaccharomyces pombe minichromosome maintenance proteins. - Gómez, Eliana B (2002)
The six conserved MCM proteins are essential for normal DNA replication. They share a central core of homology that contains sequences related to DNA-dependent and AAA(+) ATPases. It has been suggested that the MCMs form a replicative helicase because a hexameric subcomplex formed by MCM4, -6, and -7 proteins has in vitro DNA helicase activity. To test whether ATPase and helicase activities are required for MCM protein function in vivo, we mutated conserved residues in the Walker A and Walker B motifs of MCM4, -6, and -7 and determined that equivalent mutations in these three proteins have different in vivo effects in fission yeast. Some mutations reported to abolish the in vitro helicase activity of the mouse MCM4/6/7 subcomplex do not affect the in vivo function of fission yeast MCM complex. Mutations of consensus CDK sites in Mcm4p and Mcm7p also have no phenotypic consequences. Co-immunoprecipitation analyses and in situ chromatin-binding experiments were used to study the ability of the mutant Mcm4ps to associate with the other MCMs, localize to the nucleus, and bind to chromatin. We conclude that the role of ATP binding and hydrolysis is different for different MCM subunits.